Television shapes concepts of social reality among mass communication student in UiTM Rembau / Nurshahira Roslan - Roslan, Nurshahira
I am Nurshahira binti Rosian, students of Bachelor Degree (Hons.) Broadcasting in UiTM, Kampus Rembau, Cawangan Negeri Sembilan are conducting a research upon Television Shapes Concepts of Social Reality among Mass Media and Communication Students at UiTM Rembau. The purpose of this research is to gain a better understanding of how the television we watch may have an impact among the students. This is the research for academic purpose. People nowadays are gullible influence in any movie or dramas on the television. They are easily attracted and influences towards the action that has been exposed on television especially teenagers and kids. This study assumes that the role of television in influencing social reality may vary from culture to culture. In some other cases people are also argue that television viewing may not produce cultivation effects among people because of their everyday environment in neither congruent with nor reinforcing to television's message. Television is one of the symbolic that may impact in shaping or directing audiences' attitudes, habit, comprehension and other aspect of behavior. So, the researcher has been conducted a several questionnaire to answer all of the objective of this research.